The perilous gard - Pope, Elizabeth Marie, 1917-; Cuffari, Richard, 1925- (New York, N.Y., U.S.A. : Puffin Books, 1992)
In 1558 while imprisoned in a remote castle, a young girl becomes involved in a series of events that leads to an underground labyrinth peopled by the last practitioners of druidic magic.
Wilson's Children
Notable/Best Books (A.L.A.)
School Library Journal
6.1
Young Adult
Keywords: Druids and druidism -- Fiction; Druids and Druidism -- Fiction